Comparison of two different technologies measuring the same analytes in view of the In Vitro Diagnostic Regulation (IVDR) - Stierlin Noel; Hemmerle Andreas; Jung Karin; Thumfart Jörg; Risch Martin; Risch Lorenz (Journal of Laboratory Medicine)
This study systematically compared the performance and comparability of two medical laboratory analytical instruments, the conventional wet chemistry analyzer (cobas) and the dry slide technology (Vitros), across various clinical chemistry assays.